Strategi Ketahanan UMKM Menghadapi Kompetitif Bisnis Dalam Melintasi Pasca Pandemi Covid-19 Di Surabaya - Ranitawati, Endang; Widiarto, Hermono; Yahya (Owner : Riset dan Jurnal Akuntansi, 2024)
ABSTRACT2022 slowly enters a period of economic recovery in various sectors. The Covid-19 pandemic has really had an extraordinary impact, especially the business development of the MSME sector and this impact has also been felt on the domestic economy which is very significant. This can be seen in the growth rate of the economic sector in Surabaya of 4.29%, thanks to the persistence and resilience of MSME business actors the economic growth rate will increase in 2022 to 7.17% in the post-pandemic period (economic recovery period). This study aims to explore and analyze the condition of MSME business actors in Surabaya which can later be used to determine what strategic action decisions to take in order to survive facing business competition in the post-covid-19 pandemic. This study uses the analysis of the OODA loops approach as a benchmark tool in acting to defend its business in facing the competitive business world in crossing the post-pandemic Covid-19 in Surabaya. The data for this study were taken using the method of observation, interviews and questionnaires by google form respondents to several MSME business actors by means of non-probability sampling, the results of which were 87.2% believed that they could cross post-pandemic conditions Covid-19 with positive growth, an average economic recovery of 85.75%. The conclusion is that MSME entrepreneurs believe they can continue to do business in a competitive environment in the post-covid-19 pandemic.